2014
DOI: 10.1111/psyp.12200
|View full text |Cite
|
Sign up to set email alerts
|

Attention interference for emotional stimuli in cardiac interoceptive awareness

Abstract: Previous research has shown that individuals with good perception of cardiac signals, referred to as cardiac interoceptive awareness, experience emotions more intensely. To investigate if emotional experience in high cardiac interoceptive awareness arises from biases in attention, we compared the performance of participants with high versus regular cardiac interoceptive awareness in an emotional Stroop task. Participants with high cardiac interoceptive awareness showed attention interference for negative words… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Heartbeat detection accuracy using the formula described above revealed very high overall accuracy in the group (mean value = 0.92, range 0.82–0.97). However, as explained, given that heartbeat ratings used multiple choice responses, these values would be expected to be higher than those found in other studies where subjects reported the number of heartbeats without options from which to choose [Dunn et al, ; Fustos et al, ; Garfinkel et al, ; Herbert et al, ; Mirams et al, ; Pollatos et al, ; Werner et al, ]. Accordingly, the error analysis painted a slightly different picture, revealing a high overall percentage of errors (mean = 76.03%, range 41.67–100%).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Heartbeat detection accuracy using the formula described above revealed very high overall accuracy in the group (mean value = 0.92, range 0.82–0.97). However, as explained, given that heartbeat ratings used multiple choice responses, these values would be expected to be higher than those found in other studies where subjects reported the number of heartbeats without options from which to choose [Dunn et al, ; Fustos et al, ; Garfinkel et al, ; Herbert et al, ; Mirams et al, ; Pollatos et al, ; Werner et al, ]. Accordingly, the error analysis painted a slightly different picture, revealing a high overall percentage of errors (mean = 76.03%, range 41.67–100%).…”
Section: Resultsmentioning
confidence: 84%
“…For the HB condition, accuracy calculations utilized a formula frequently used for heartbeat tracking tasks [Cali et al, 2015;Chong et al, 2016;Dunn et al, 2012;Fustos et al, 2013;Garfinkel et al, 2015;Grabauskaite et al, 2017;Herbert et al, 2007;Mirams et al, 2012;Pollatos et al, 2005Pollatos et al, , 2007aWerner et al, 2009Werner et al, , 2014: 1-(|number of actual heartbeats 2 number of reported heartbeats|/number of actual heartbeats). This formula yields a number between 0 and 1, with 1 representing perfect interoceptive accuracy and any values 0.85 thought to reflect high IA [Herbert et al, 2007;Pollatos et al, 2005Pollatos et al, , 2007aWerner et al, 2009Werner et al, , 2014. However, given that our task implementation used a multiple-choice response for reporting heartbeats [Ernst et al, 2013], there was by design a limit on how much the response could deviate from the actual number of heartbeats, and thus IA appeared to be quite high when utilizing this formula.…”
Section: Behavioral Measuresmentioning
confidence: 99%
“…The reliability of the score has been repeatedly confirmed. 9,49 Cued reaction time (RT) and mental arithmetic tasks were applied to assess attentional and executive function. In the cued RT task, subjects were instructed to respond to a cross on a computer screen (imperative stimulus) as quickly as possible via a key stroke.…”
Section: Assessment Of Interoceptive Awareness and Cognitive Testingmentioning
confidence: 99%
“…[5][6][7] In addition, they demonstrated enhanced memory for emotional words, 8 were more affected by emotional stimulation with respect to cognitive processing, and showed improved coping during aversive 4 social situations. 9,10 Outside of the field of emotion, high interoceptive individuals performed better on neuropsychological tasks quantifying basic and higher cognitive functions. 11,12 Additional correlates of accurate interoceptive awareness include a more positive body image, assessed via questionnaires, and reduced proneness to experimentally induced distortions in body scheme.…”
Section: Introductionmentioning
confidence: 98%
“…A growing body of research has shown that interoceptive awareness is implicated in decision making (Dunn, Evans, Makarova, White, & Clark, 2012; Dunn, Galton et al 2010; Kirk, Downar, & Montague, 2011; Werner, Jung, Duschek, & Schandry, 2009), affect regulation (Füstös, Gramann, Herbert, & Pollatos, 2013; Sze, Gyurak, Yuan, & Levenson, 2010), and in other domains of cognitive and behavioral functioning (Herbert et al, 2010; Pollatos & Schandry, 2008; Pollatos, Schandry, Auer, & Kaufmann, 2007; Werner, Mannhart, Reyes Del Paso, & Duschek, 2014; Werner, Peres, Duschek, & Schandry, 2010). Specifically, Kirk et al (2011) found that interoception drives increased rational decision-making while playing the ultimatum game, a two-person monetary exchange task.…”
Section: Introductionmentioning
confidence: 99%